-3(-5v+6)-3v=2(v-4)-2

Simple and best practice solution for -3(-5v+6)-3v=2(v-4)-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(-5v+6)-3v=2(v-4)-2 equation:


Simplifying
-3(-5v + 6) + -3v = 2(v + -4) + -2

Reorder the terms:
-3(6 + -5v) + -3v = 2(v + -4) + -2
(6 * -3 + -5v * -3) + -3v = 2(v + -4) + -2
(-18 + 15v) + -3v = 2(v + -4) + -2

Combine like terms: 15v + -3v = 12v
-18 + 12v = 2(v + -4) + -2

Reorder the terms:
-18 + 12v = 2(-4 + v) + -2
-18 + 12v = (-4 * 2 + v * 2) + -2
-18 + 12v = (-8 + 2v) + -2

Reorder the terms:
-18 + 12v = -8 + -2 + 2v

Combine like terms: -8 + -2 = -10
-18 + 12v = -10 + 2v

Solving
-18 + 12v = -10 + 2v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-2v' to each side of the equation.
-18 + 12v + -2v = -10 + 2v + -2v

Combine like terms: 12v + -2v = 10v
-18 + 10v = -10 + 2v + -2v

Combine like terms: 2v + -2v = 0
-18 + 10v = -10 + 0
-18 + 10v = -10

Add '18' to each side of the equation.
-18 + 18 + 10v = -10 + 18

Combine like terms: -18 + 18 = 0
0 + 10v = -10 + 18
10v = -10 + 18

Combine like terms: -10 + 18 = 8
10v = 8

Divide each side by '10'.
v = 0.8

Simplifying
v = 0.8

See similar equations:

| -4(3x+1)=-136 | | 4/x=1/5 | | 0.62-0.15x=0.25-0.1 | | f(x)=2x-3x+4 | | -7x+3=-11 | | -15-5t=15 | | 5x-4(-3/2x+2)=y | | 5x-5=12-68 | | f(x)=2x(4)-3x+4 | | 4x+13=8x+25 | | -x+42=4x | | -2.5+g=-1.3-1.1 | | (3x+4)(5x+9)= | | 36=8-7y | | 0.5x+1.2=0.8x-1.2 | | .75x=36.75 | | 9x+14=5x+2 | | x/3+x/6=5 | | g=7*1/2 | | 13(x+6)-3=3+-5 | | -0.10(33)+0.85x=0.05(x-2) | | f--40=-12 | | .15x=5.25 | | 3(8+2x)(5+2x)=(14.5+2x)(15+2x) | | x^2-7x+12.25=.25 | | 3(n+2)=6-3(n+4) | | 4(20-2n)=4 | | 6x^2=3x+30 | | x-4/3+4/3=-x/2 | | 61/4-32/3 | | 2/7x=2 | | 497-x/3 |

Equations solver categories